PENGARUH MEDIA GALERI IMERSIF DAN KUIS INTERAKTIF TERHADAP PENINGKATAN PENGETAHUAN GIZI ANAK SEKOLAH DASAR - Eliana, Desy; Isriyatil Jannah, Putri (Journal of Health Service Management, 2026)
Background: Good nutritional knowledge among elementary school children plays an essential role in supporting healthy physical growth and cognitive development. However, many children still have limited understanding of nutrition due to monotonous learning approaches that do not stimulate engagement. Innovative tools such as immersive gallery media and interactive quizzes have the potential to enhance learning experiences by providing visual, enjoyable, and participatory activities.. Objective: This study aimed to examine the effect of immersive gallery media and interactive quizzes on improving nutritional knowledge among elementary school students Methods: This research used a quasi-experimental one-group pretest–posttest design involving 26 second-grade students from SDICT Al Abidin Surakarta. Nutritional knowledge was measured using a 15-item questionnaire. Data analysis included the Shapiro–Wilk test to assess normality and the paired sample t-test to compare pretest and posttest scores Results: The findings showed an increase in the mean knowledge score from 57.12 before the intervention to 76.92 after the intervention. The statistical test yielded p = 0.000 (p < 0.05), indicating a significant improvement in nutritional knowledge following the use of immersive gallery media and interactive quizzes. Conclusions: In conclusion, immersive gallery media and interactive quizzes are effective learning tools that significantly enhance students’ nutritional knowledge. These methods are recommended as engaging and developmentally appropriate innovations for nutrition education, although further research with larger samples and control groups is needed to strengthen generalization.